2021
DOI: 10.1053/j.ajkd.2020.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth for Home Dialysis in COVID-19 and Beyond: A Perspective From the American Society of Nephrology COVID-19 Home Dialysis Subcommittee

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 29 publications
2
76
0
3
Order By: Relevance
“…Prior to COVID-19, the use of telemedicine to perform renal clinics was shown to be accepted by clinicians with benefits of reduced travel time, more efficient use of staff time, and a strong sense of job satisfaction being reported [ 62 ], akin to other clinical specialties [ 63 , 64 , 65 ]. A recent publication by the American Society of Nephrology outlined the expectation for telemedicine to remain within renal medicine in some form following the COVID-19 pandemic and associated restrictions [ 66 ]. Moreover, a similar study conducted during COVID-19 in renal clinicians also reported widespread support for telemedicine, reporting more efficient use of staff time, reduced travel, peace of mind and a strong sense of job satisfaction [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior to COVID-19, the use of telemedicine to perform renal clinics was shown to be accepted by clinicians with benefits of reduced travel time, more efficient use of staff time, and a strong sense of job satisfaction being reported [ 62 ], akin to other clinical specialties [ 63 , 64 , 65 ]. A recent publication by the American Society of Nephrology outlined the expectation for telemedicine to remain within renal medicine in some form following the COVID-19 pandemic and associated restrictions [ 66 ]. Moreover, a similar study conducted during COVID-19 in renal clinicians also reported widespread support for telemedicine, reporting more efficient use of staff time, reduced travel, peace of mind and a strong sense of job satisfaction [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…implemented telemedicine consultation for radiation-oncology and effectively lessoned the in person visit from 100% to 21% [195] . The rapid developments in supportive technologies are the future of TM including POC diagnostics and laboratory measurements to care the patients effectively while staying at their home [196] .…”
Section: Preventive Strategies For Covid-19mentioning
confidence: 99%
“…Some of these challenges include adequate provider, clinician, and patient education, access to telehealth technologies, a lack of home dialysis "champions," and a need to further empower and train patients and their caregivers to take an active role in their care. [29][30][31] Specific to the COVID-19 pandemic, some kidney disease leaders expressed concern that physicians were unable to conduct certain procedures required for the initiation of home dialysis, particularly PD due to regulatory constraints related to prioritization of catheter procedures. 32 As a consequence, candidates for PD are often forced, either to opt for in-center hemodialysis or postpone the start of a necessary treatment.…”
Section: International Standards and Cooperationmentioning
confidence: 99%